LEGAL FRAMEWORK FOR COOPERATION BETWEEN THE REPUBLIC OF UZBEKISTAN AND THE KYRGYZ REPUBLIC (American Journal of Pedagogical and Educational Research, 2025)
The legal basis for cooperation between the Republic of Uzbekistan and the Kyrgyz Republic is founded on a number of international treaties and agreements that regulate various aspects of their bilateral relationship. For example, the Treaty on Eternal Friendship between the Republic of Uzbekistan and the Kyrgyz Republic, signed on December 24, 1996, is a fundamental document that lays the groundwork for the comprehensive development of cooperation between the two states. It enshrines the principles of sovereignty, territorial integrity, non-interference in each other's internal affairs, and the commitment to peaceful dispute resolution.As of January 24, 2023, the two countries have signed 213 foundational documents, with 22 of them signed during President Sadyr Japarov's state visit to Uzbekistan in March 2021. The main documents that have established a strong basis for friendly relations are the Treaty on Eternal Friendship of December 24, 1996, and the Declaration on Strategic Partnership, Friendship, Good-Neighborliness, and Strengthening Trust of October 5, 2017. These documents affirm the core principles of bilateral cooperation: equality, mutual respect for independence and state sovereignty, non-interference in each other's internal affairs, and a shared desire to establish mutually beneficial economic partnerships at both the state level and among business entities.